Eksistensi Peraturan Pemerintah Pengganti Undang-Undang dan Kewenangan Mahkamah Konstitusi Dalam Pengujian - Muhammad Rum Siolimbona; Saartje Sarah Alfons; Hendrik Salmon (Postgraduate Program in Law, Universitas Pattimura, 2022)
Introduction: The 1945 Constitution of the Republic of Indonesia does not have a provision that gives the Constitutional Court the authority to examine Government Regulations in Lieu of Laws but in fact the Constitutional Court examines Government Regulations in Lieu of Laws.Purposes of the Research: the purpose of this article is to find out the existence of government regulations in lieu of laws and the authority of the Constitutional Court to examine government regulations in lieu of laws.Methods of the Research: This study uses a normative juridical method with a statute approach, a conceptual approach, and a case approach.Results of the Research: Hierarchically, government regulations in lieu of laws are parallel to laws and serve to replace laws that were issued in the event of a compelling emergency. The content material contained in the Government Regulation in Lieu of Law is the same as the Law. The Constitutional Court is based on Law Number 48 of 2009 concerning Judicial Power, where a judge cannot reject a case that is brought to him on the grounds that there is no law. According to the principle of ius curia novit, the judge can conduct rechtvinding. The essence of the establishment of the Constitutional Court is to guarantee human rights, for that the Constitutional Court must fulfill the constitutional rights of citizens, by which the testing of Government Regulations in Lieu of Law by the Constitutional Court is allowed and does not violate the law.